1944
DOI: 10.1172/jci101464
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Hypertonicity: Alterations in the Distribution of Body Water, and the Cause of Death 1

Abstract: In dogs deprived of food and water, water is lost out of proportion to the loss of salt. Concentrations of sodium and of chloride in serum therefore rise progressively for many days, until, just before death, concentrations as high as 186 m.Eq. of sodium and 133 m.Eq. of chloride per liter of serum have been found (1). It was not, however, clear whether death was due to the hypertonicity of the body fluids or to the concomitant dehydration. In certain of the present experiments, a comparable degree of hyperton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1944
1944
1973
1973

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…Our experiments reported here and elsewhere (1,18,19) give some negative and some positive clues to the factors common to all the diverse states in which there may be a loss of excess potassium. It cannot simply be the result of a temporary increase of plasma volume, since it is absent following intravenous injections of isotonic and hypotonic solutions (Table I, Experiments llC, 13A, 14) and since it appears as readily after intraperitoneal as after intravenous injections of hypertonic salt solutions (Tables II and III).…”
Section: Discussionsupporting
confidence: 51%
“…Our experiments reported here and elsewhere (1,18,19) give some negative and some positive clues to the factors common to all the diverse states in which there may be a loss of excess potassium. It cannot simply be the result of a temporary increase of plasma volume, since it is absent following intravenous injections of isotonic and hypotonic solutions (Table I, Experiments llC, 13A, 14) and since it appears as readily after intraperitoneal as after intravenous injections of hypertonic salt solutions (Tables II and III).…”
Section: Discussionsupporting
confidence: 51%
“…Nadal et al showed in 1941 that the peripheral circulatory failure seen in salt deficiency was due to the reduction in the extracellular fluid volume, and that in water deficiency water is lost from both compartments; Marriott (1947) also explained the clinical picture of dehydration, from whatever cause, on the basis of loss of extracellular fluid. But Gamble (1944) and Winkler, Elkinton, Hopper & Hoff (1944) The intracellular over-hydration that occurs when salt is not replaced and water losses are either replaced or not very high is analogous to that described by Danowski, Winkler & Elkinton (1946) in over-hydrated dogs. These animals developed convulsions, the so-called water intoxication; it is possible that 'heat cramps' in man may be the same condition; in the long series of tests, of which the thirty here described are a small proportion only, the conditions for intracellular over-hydration were frequently fulfilled and 'heat cramps', fully developed or incipient, were a regular complaint.…”
Section: Methodsmentioning
confidence: 81%
“…Finally, 2 dogs (25B, 29), initially dehydrated by prolonged withdrawal of food and water, subsequently received repeated intraperitoneal injections of a 5 per cent sodium chloride solution. Certain data from these last 2 experiments have been published elsewhere (11).…”
Section: Methodsmentioning
confidence: 99%